Korelasi antara gaya mengajar guru dengan self-efficacy siswa sekolah dasar - Intan Kamila Zahra; Hawwin Fitra Raharja (Prodi Pendidikan Guru Sekolah Dasar, 2026)
Academic self-efficacy is one of the psychological factors that influences student learning achievement in primary school; however, the factors that shape it remain not fully understood, including the role of teachers' teaching styles. This study aimed to analyze whether there is a correlation between teachers' teaching styles and the self-efficacy of fifth- grade primary school students. A correlational quantitative approach was employed using total sampling of 27 fifth-grade students at SD Negeri Gajah II Ngoro Jombang in the 2025/2026 academic year. Data were collected through closed Likert-scale questionnaires for both variables and analyzed using descriptive statistics and Pearson Product Moment correlation with SPSS version 25.0, following Shapiro-Wilk normality tests (teaching style sig. = .094; self-efficacy sig. = .110) and linearity tests (Deviation from Linearity sig. = .155). Descriptive results showed that both teaching style and student self-efficacy were in the moderate category, each with a dominant percentage of 63.0%. Correlation analysis yielded r = .184 with a significance value of .359 > .05 and t-value = .936 < t-table = 2.060, leading to the acceptance of H0. Therefore, no significant positive correlation was found between teachers' teaching styles and students' self-efficacy. These findings suggest that primary school students' self-efficacy is more strongly influenced by multidimensional factors such as mastery experiences, family support, and intrinsic motivation rather than teaching style variations alone. Future research is recommended to involve larger and more diverse samples while considering mediating variables such as learning motivation and family support.